Maturity Business Process Management at Companhia Energética de Minas Gerais - Neves, Mayra Evangelista; Parreiras, Fernando Silva; Ferreira, Eric de Paula; Corrêa, Fábio (Revista Gestão da Produção Operações e Sistemas, 2021)
Purpose: This study aims to assess the maturity of Companhia Energética de Minas Gerais in business process management. Theoretical framework: Business Process Management is an alternative to the standard departmentalized structure. This alternative presents Maturity in Processes as the degree of explicit definition, management, measurement, control and effectiveness that a process has. Thus, this Maturity excels in assessing the current situation in order to direct improvement initiatives and control the development of what is being measured. Design/methodology/approach: Data was collected through a questionnaire, obtaining a sample of 729 respondents, and the data was analyzed using the structural equation modeling technique. Findings: The company being studied is at level 4, and is called quantitatively managed, where the promotion of actions to recognize those responsible for the processes and alignment of information systems to customer needs are some of the actions needed to increase this stage. Research, Practical & Social implications: Through the maturity identified, Companhia Energética de Minas Gerais can promote actions to improve its processes, resulting in social impacts arising from the provision of services to the community. Originality/value: From a theoretical perspective, this study contributes by making use of a maturity model and by showing its results for comparisons between companies; because, empirically, it contributes to that company so that it is aware of its current stage and actions to increase that stage. Keywords: BPM; business process management; BPMMM; maturity model; electrical sector.